Postcoital ingestion of the aqueous extract of Erythrina falcata Benth prevents pregnancy in the mouse - Orihuela P.A. (2006)
We thank Dr. Horacio B. Croxatto from the Instituto Chileno de Medicina Reproductiva for his valuable comments in the preparation of this manuscript. This work received financial support from grants CONCYTEC 628 DE-89 and 2043 DE-91, and FONDECYT 1030315.